Is RIRS Safe and Efficient In Patients With Kidney Stones Who Had Previous Open, Endoscopic, or Percutaneous Kidney Stone Surgery? One Center Retrospective Study - Baylan, Burhan; Sari, Sercan; Cakici, Mehmet Caglar; Selmi, Volkan; Özdemir, Harun; Ozok, Hakki Ugur; Karakoyunlu, Ahmet Nihat; Topaloglu, Hikmet; Sagnak, Azmi Levent; Ersoy, Hamit (Urology Journal, 2020)
Purpose: In our study, we assessed the efficiency and reliability of retrograde intrarenal surgery secondary to open surgery for kidney stone treatment. Moreover, we compared the efficiency and safety of retrograde intrarenal surgery for the patients with previous history of open surgery, percutaneous nephrolithotomy, secondary retrograde intrarenal surgery (RIRS) and primary RIRS. Materials and Methods: Data was retrospectively reviewed. Patients who had kidney anomalies, who had been stented due to ureteral stricture in the operation and who were < 18 years old, were excluded. There were 30 patients who underwent RIRS secondary to open surgery. The demographic and stone characteristic as well as intraoperative and postoperative data of the patients were recorded. 30 patients with similar demographic and stone characteristics to those patients were selected by match pairing method from patients who had previous PNL, RIRS history and had undergone primary RIRS. A total of 120 patients, in total 4 groups, were included in the study. Results: Statistically significant difference was detected among the groups with regards to shock wave lithotripsy history and preoperative JJ stent rate. There was no statistically significant difference in terms of stone characteristics, intraoperative and postoperative data. Conclusion: RIRS is an efficient and safe method for kidney stone treatment of the patients with previous history of open surgery, percutaneous nephrolithotomy and retrograde intrarenal surgery. It has a similar efficiency and safety for the patients who have undergone retrograde intrarenal surgery. This is the first study that compares the patients especially with different previous surgery methods.